2016
DOI: 10.1182/blood-2015-11-679134
|View full text |Cite
|
Sign up to set email alerts
|

Ibrutinib enhances chimeric antigen receptor T-cell engraftment and efficacy in leukemia

Abstract: Key Points Ibrutinib treatment of CLL enhances the generation of CAR T cells for adoptive immunotherapy. Concurrent ibrutinib therapy improves the engraftment and therapeutic efficacy of anti-CD19 CAR T cells in mouse models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
331
0
13

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 409 publications
(373 citation statements)
references
References 51 publications
9
331
0
13
Order By: Relevance
“…Another recent study investigating the effect of ibrutinib on chimeric antigen receptor-expressing T cells demonstrated that defects in T-cell proliferation and activation were improved after 5 to 11 cycles of ibrutinib therapy. 37 Thus, it is possible that direct elimination of CLL through ibrutinib Bruton's tyrosine kinase targeting reduces T-cell exhaustion, leading to more effective T-cell immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Another recent study investigating the effect of ibrutinib on chimeric antigen receptor-expressing T cells demonstrated that defects in T-cell proliferation and activation were improved after 5 to 11 cycles of ibrutinib therapy. 37 Thus, it is possible that direct elimination of CLL through ibrutinib Bruton's tyrosine kinase targeting reduces T-cell exhaustion, leading to more effective T-cell immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Combining CAR T cells with targeted agents that have immune modulating activity may also prove beneficial. For example, recent work has demonstrated that CAR T cells made from patients with CLL have greater proliferative potential when harvested after prolonged treatment with ibrutinib and that ibrutinib enhances CAR T cell activity in mouse models [71]. The last several decades have seen dramatic innovation in CAR design, manufacturing, and clinical applications.…”
Section: Discussionmentioning
confidence: 99%
“…They found that CAR T-cell function is not impaired with the exposure of ibrutinib in vitro and in fact simultaneous administration improves tumor clearance, CAR T-cell engraftment and survival in human xenograft models of resistant ALL and CLL. This finding indicates that clinical trials with combination therapy are warranted as ibrutinib enhances CAR T-cell function [15]. Targeting BCL-2 through venetoclax is a significant first step approach can be acquired for the therapeutic strategy in CLL.…”
Section: Short Communicationmentioning
confidence: 99%